Awareness in the development of intercultural competences and existing Relationships between attitudes, skills and knowledge - Italo Cavalcante Aguiar; Romulo Alves Soares; Luis Eduardo Brandão Paiva; Bruno de Souza Lessa; Tim Rubert; José Carlos Lázaro da Silva Filho (Revista Gestão Universitária na América Latina)
This research aims to examine how the exchangeists' perceptions about their abilities, knowledge and attitudes influence their awareness. In view of this, the theoretical methodological basis of Fantini (2007) is used, guided by his model of Intercultural Competence Assessment (ACI). To this end, the German and Spanish students who took part in an exchange program at the Federal University of Ceará (UFC) between 2008 and 2015 were chosen to measure their developed intercultural competences. It was obtained a sample of 159 foreign students, who exchanged in the UFC. For the treatment of the data, in addition to the descriptive and inferential statistics, the multivariate analysis of the data is used. Thus, the results show that Knowledge positively influences the students' awareness at the beginning and end of the exchange, while the Skills will negatively influence the awareness at the end of the exchange. The Attitudes component that at the beginning of the exchange influenced negatively the students' awareness at the end of the exchange began to influence positively.